The Cambridge Guide to Reading Poetry - Hodgson, Andrew (Cambridge : Cambridge University Press, 2021)
Aimed at students and readers of poetry at all levels, 'The Cambridge Guide to Reading Poetry' takes a tour through a galaxy of examples, demonstrating how to come to terms with poetry's verbal, formal, emotional, and conceptual power. It shows how reading poems enhances our enjoyment and understanding of life.
Keywords: Poetics; Literature